Development and validation of Malaysian communication style instrument - Mustaffa, Che Su; Abu Bakar, Hassan; Ahmad, Mohd Khairie; Mohd Hadza @ Othman, Mohd Baharudin; Ibrahim, Marzura (Canadian Center of Science and Education, 2014)
The Malaysian Malay Communication Style (MMCS) formulated by Che Su and Hassan (2010) was developed to measure specific Malay communication characteristics in the workplace.We extended this work by using structural equation modelling to determine the factor structure of the 60-item version of the MMCS.Based on a sample of 320 employees, we found eight stable dimensions which measure communication style among Malay employees in Malaysian contexts. Moreover, scores on the scale developed to measure the MMCS criteria yielded excellent validity and reliability estimates.This study provided and presented insights and further understanding of communication style from the indigenous perspective, which allows practitioners to gain in-depth knowledge about the implementation of organizational communication in an organization.The implications of this research were discussed.